3(x+8)+9=3x+6

Simple and best practice solution for 3(x+8)+9=3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+8)+9=3x+6 equation:


Simplifying
3(x + 8) + 9 = 3x + 6

Reorder the terms:
3(8 + x) + 9 = 3x + 6
(8 * 3 + x * 3) + 9 = 3x + 6
(24 + 3x) + 9 = 3x + 6

Reorder the terms:
24 + 9 + 3x = 3x + 6

Combine like terms: 24 + 9 = 33
33 + 3x = 3x + 6

Reorder the terms:
33 + 3x = 6 + 3x

Add '-3x' to each side of the equation.
33 + 3x + -3x = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
33 + 0 = 6 + 3x + -3x
33 = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
33 = 6 + 0
33 = 6

Solving
33 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 13+7n=4n+4 | | 8n-5-2n=41 | | Y=x^2+-1 | | 2x-11=10x+13 | | (5)x*x+27x+10=0 | | (5)x*x+27+10=0 | | (x+6)(x+7)=(11+x)(4+x) | | 9-6*-.5=14+4*-.5 | | -3x+2(2x+4)=6(x+8)+15 | | 67x+25=350 | | -y=p | | x-0.2(x)=18 | | -5-(15y-1)=14y-32-y | | 5x(2x-10)=35 | | 6y^2+17y-3=0 | | 4z-6z+8z=6z | | 4(x-9)-3(x-15)=2x-3 | | 9-6x=14+4x | | 5x-7=x+3 | | 2x+14-(x+1)=0 | | (6)n*n+7n=20 | | (6)n*n+7n=0 | | 1x+10+8=4 | | 15-g=23-29 | | (6)n*n+7n-20=0 | | (6)n*n+7-20=0 | | 2x+4(x-6)=-11-5(x-4) | | 3x^4=1536x | | 5x+7=-7+2x+20 | | 3+7(x-9)=3x-4 | | 6+2x-(x-3)=4(x-1)+22 | | 2-5(x+1)=9+x |

Equations solver categories